Analisis Minat Penggunaan Surat Elektronik Kedinasan Pada Organisasi Sektor Publik (Studi Kasus Balai Diklat Keuangan Makassar) - Rahmaluddin Saragih; Azwar Iskandar (Program Studi Administrasi Negara Universitas Serang Raya, 2019)
This research aims to evaluate the factors that influenced the behavioral intensity of apparatus for using official electronic mail in public organization based on perceived user with Theory Acceptance Model approach. Data used in this research is primary data by using questionaire. Sample collection methods used in this research was random sampling technique. Data analysis in this research uses Structural Equation Modelling (SEM) with component or varian based with Partial Least Square. The result showed that perceived ease of use significantly positive influence to perceived usefulness, perceived ease of use significantly positive influence to attitude toward using, perceived usefulness significantly positive influence to attitude toward using, behavioral intention to use significantly positive influence to actual system usage. In the other correlation path, this research also show that perceived usefulness has no significant effect on behavioral intention to use, and attitude toward using has no attitude toward using behavioral intention to use.